2021
DOI: 10.1177/03000605211013209
|View full text |Cite
|
Sign up to set email alerts
|

Adverse birth outcomes and associated factors among mothers who delivered in Bale zone hospitals, Oromia Region, Southeast Ethiopia

Abstract: Objective Adverse birth outcomes, which include stillbirth, preterm birth, low birthweight, congenital abnormalities, and stillbirth, are the leading cause of neonatal and infant mortality worldwide. We assessed adverse birth outcomes and associated factors among mothers who gave birth in Bale zone hospitals, Oromia, Southeast Ethiopia. Methods We used systematic random sampling in this cross-sectional study. We identified factors associated with adverse birth outcomes using bivariate analysis and multivariabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
1
17
1
1
Order By: Relevance
“…5 A systematic review and metaanalysis study in Sub-Saharan Africa reported a pooled prevalence of 29.7%. 6 Besides, the magnitude of perinatal complication was 18.2% in Butajira, 7 21% in Bale Zone, 8 and 18.3% in Hawassa town. 9 Further, in Southern Ethiopia, one-fourth (24.9%) of multiparous women had at least one adverse birth outcome.…”
Section: Introductionmentioning
confidence: 94%
“…5 A systematic review and metaanalysis study in Sub-Saharan Africa reported a pooled prevalence of 29.7%. 6 Besides, the magnitude of perinatal complication was 18.2% in Butajira, 7 21% in Bale Zone, 8 and 18.3% in Hawassa town. 9 Further, in Southern Ethiopia, one-fourth (24.9%) of multiparous women had at least one adverse birth outcome.…”
Section: Introductionmentioning
confidence: 94%
“…But, the current study, included more adverse events, i.e., obstructed labor, retained placenta, hypertension in pregnancy, low birth weight, stillbirth, macrosomia, malpresentation, and prematurity. In addition, the finding was higher than 24.5% in Hosanna town [11], 21% in Bale Zone [12], and 18.3% in Hawassa town [13]. The variation might be due to the differences in sample size and study setting.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, in Southern Ethiopia, 8.6% of birth outcomes were preterm birth, 9.8% were low birth weight and 8.6% were stillbirths [11]. Further, in Bale Zone, low birth weight (12.2%), preterm birth (8.5%), stillbirth (7.8%), and congenital anomaly (3.1%) were common adverse birth outcomes [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations